Perceptions of university students on critical thinking skills (Praxis Educativa, 2024)
This research aims to describe the level of development of critical thinking skills perceived by students at the National University of Pilar (UNP). The approach was quantitative, with an observational and cross-sectional design. The population included 2950 students from seven academic units. The sample was 341 units, determined with a margin of error of 5 %, a confidence level of 95 %, stratified and randomly selected by telephone dialing. We use the Google questionnaire until we complete the required amount for each stratum. We apply the instrument validated by Canese (2020) of critical thinking skills. We found that the students reached an intermediate level (62 %) in all skills, the level degrading according to the complexity of the thought process required. This reveals the need to enhance these critical thinking skills from the academy.
Keywords: critical thinking, reading comprehension, analysis, intellectual empathy, evaluation.